The Effect of Sex and Wealth on Population Attributable Risk Factors for Dementia in South Africa - Bobrow, Kirsten; Hoang, Tina; Barnes, Deborah E.; Gardner, Raquel C.; Allen, Isabel E.; Yaffe, Kristine (Frontiers in Neurology, 2021)
Background and aims: South Africa is a middle-income country with high levels of income inequality, a rapidly aging population, and increasing dementia prevalence. Little is known about which risk factors for dementia are important and how they differ by social determinants of health like sex and wealth. We calculate the population attributable risks (PAR) for established potentially modifiable risk factors for dementia among these different groups. Methods: We obtained risk factor prevalence from population-based surveys for established dementia risk factors (diabetes, midlife hypertension, midlife obesity, physical inactivity, depression, smoking, low educational attainment, social isolation.) We used relative risk estimates reported in previous meta-analyses and estimated PARs using Levin’s formula and accounting for communality. We tested for interactions by sex and wealth. Results: The prevalence of established risk factors for dementia ranged from 5% for depression to 64% for low education. Accounting for communality, the risk factors contributing the greatest PAR were low education (weighted PAR 12%, 95% CI 7% to 18%), physical inactivity (9%, 5% to 14%), and midlife hypertension (6%, 5% to 14%). Together, 45% of dementia cases may be attributable to modifiable risk factors (95% CI 25% to 59%). We found significant interactions between sex, wealth, or both and each risk factor except social isolation and physical activity. Low education PAR was inversely associated with wealth. PAR for midlife hypertension, obesity, and diabetes increased with wealth and was higher in women. The PAR for smoking was higher in men (8% vs 2%) and increased with wealth among women only. We found that either strategy of targeting selected risk factors with the highest PAR (hypertension, smoking, physical inactivity) or small reductions across all risk factors could potentially reduce as many as 250 000 dementia cases over the coming decades. Discussion: The potential impact on dementia risk by decreasing exposure to established dementia risk factors is large and differs by sex and wealth. Risk factor PAR should inform national and local health policy dementia initiatives in South Africa including which risk factors to target in the whole population and which to target in high-risk groups for maximum public health benefit.